2009
DOI: 10.1189/jlb.0209107
|View full text |Cite
|
Sign up to set email alerts
|

The sympathetic nervous system modulates CD4+FoxP3+ regulatory T cells via a TGF-β-dependent mechanism

Abstract: CD4(+)FoxP3(+) Tregs are essential mediators of the peripheral immune response to self-antigens. Accordingly, the homeostatic regulation of Treg activity and number would impact on the immune response to both self- and non-self antigens. Because the sympathetic nervous system (SNS) interacts chemically and physically with the central and peripheral immune system and exerts a direct influence on antigen-presenting cells and effector lymphocytes, we have investigated the effect of chemical ablation of the SNS on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 56 publications
5
40
0
1
Order By: Relevance
“…produced an 84% decrease in splenic norepinephrine 40 and has been used in numerous studies, contributing to what is now a large body of evidence demonstrating an interaction between the sympathetic nervous system and immune function. [41][42][43] In our studies, splenic denervation via splenic injections of 6-OHDA completely abolished the protective effect of ultrasound in IRI, strongly suggesting that ultrasound reduces IRI in a catecholaminergic-dependent and presumably splenic nerve-dependent manner. The immune modulatory effect of splenic chemical sympathectomy produced by systemic administration of 6-OHDA, increased splenocyte proliferation and cytokine production, was blocked by pretreating animals with desipramine, a norepinephrine reuptake inhibitor that blocks uptake of 6-OHDA into nerve terminals, suggesting that the effects of 6-OHDA were mediated neuronally.…”
Section: Neural Control Of Inflammationsupporting
confidence: 59%
“…produced an 84% decrease in splenic norepinephrine 40 and has been used in numerous studies, contributing to what is now a large body of evidence demonstrating an interaction between the sympathetic nervous system and immune function. [41][42][43] In our studies, splenic denervation via splenic injections of 6-OHDA completely abolished the protective effect of ultrasound in IRI, strongly suggesting that ultrasound reduces IRI in a catecholaminergic-dependent and presumably splenic nerve-dependent manner. The immune modulatory effect of splenic chemical sympathectomy produced by systemic administration of 6-OHDA, increased splenocyte proliferation and cytokine production, was blocked by pretreating animals with desipramine, a norepinephrine reuptake inhibitor that blocks uptake of 6-OHDA into nerve terminals, suggesting that the effects of 6-OHDA were mediated neuronally.…”
Section: Neural Control Of Inflammationsupporting
confidence: 59%
“…Indeed, convincing evidence suggests that it is possible for CAs (stress) to affect Tregs in in vivo environment and in ex vivo cultures (22,34,35). The effects of CAs on Tregs are achieved through both indirect and direct mechanisms.…”
Section: The Journal Of Immunologymentioning
confidence: 99%
“…One in vitro study has shown that NE can decrease or increase hepatocyte production of TGF-b in a dose-dependent manner (36). Bhowmick et al (34) suggested that the number of peripheral Tregs is mediated by sympathetic nervous system signals, and TGF-b acts as a bridge between the sympathetic nervous and immune systems. And TGF-b was decreased in PBMCs by short-term exposure to E at 24 h, whereas it was increased at day 11 in long-term E cultures; a significant increase in the expression of FOXP3 mRNA in cultures subjected to 11 d of E exposure has also been observed (22).…”
Section: The Journal Of Immunologymentioning
confidence: 99%
“…CA can modulate the proliferation and differentiation of immune cells, as well as cytokine production (Flierl et al, 2008;Peng et al, 2004;Torres et al, 2005). In this context, the sympathetic nervous system is also able to modulate the induction of Treg cells (Bhowmick et al, 2009) via a TGF-β-dependent mechanism, thus acting as a bridge between the immune and the nervous systems.…”
Section: The Neuroimmune Systemmentioning
confidence: 99%